Gestión de directores y cultura organizacional en instituciones educativas de secundaria - Red N° 07 del Callao - Martínez Martínez, Carmen Teresa (2010)
This research aims to measure the relationship between the variable educational management of directors and the variable organizacional culture of teachers new forms of organizational culture that would allow the conduct I.E. effective and efficient way to do it we use a research design, descriptive, correlational applied to a populación of 189 people. There were two questionnaries making a total 77 questions which allow to determine the degree of meidenful it also used systemiic approach to management the variable Educational Management and humanistic approach to measure organizational culture supported by Robbins ,the results demostrate the reability of both variables it stated in the results concluding in a precise way ,thus validatimng the Works done on the netwolrk Nª 7 Callao.